1939-1945 : We have not forgotten = Nous n'avons pas oublié = Wir haben es nicht vergessen : abridged edition - Mazur, Tadeusz; Tomaszewski, Jerzy (Warszawa: Polonia, 1961)
"Materials collected and edited by Tadeusz Mazur, Jerzy Tomaszewski Bibliotheek Camille Huysmans"